Investigation of Alfvén eigenmodes and energetic particle modes in EAST with neutral beam injection. (17th May 2021) - Xu, Liqing; Shen, Wei; Ren, Zhenzhen; Zhou, Tianfu; Wang, Yifeng; Hui, Lian; Zhang, Dingzong; Huang, Yueheng; Hu, Youjun; Hao, Baolong; Zang, Qing; Zhu, Xiang; et al.
Abstract: Alfvén eigenmodes (AEs) and energetic particle modes (EPMs) have been observed in EAST neutral beam injection plasma with the presence of heavy tungsten impurity in the core region. The AEs are identified as toroidal Alfvén eigenmodes (TAEs) with roughly constant frequency f TAE ∼ 100 kHz and a special set of AEs with frequency chirping up from frequency f AE ∼ 70 kHz to f AE ∼ 100 kHz. The frequency of EPMs is around f EPM ∼ 60 kHz, exhibiting with frequency chirping down feature. A transition from EPMs to AEs is found, and the location and mode numbers are measured by experimental diagnostics. Hybrid simulations with the global kinetic-magnetohydrodynamic code M3D-K have been carried out to investigate the observed AEs and EPMs, and linear simulations find the EPM with toroidal mode number n = 2 and poloidal mode number m = 3. Nonlinear simulations show that the EPM frequency chirps down nonlinearly, and then two modes emerge with frequencies around 72.7 kHz and 88.0 kHz: the mode with higher frequency is a TAE, and the other mode is an EPM. Afterward, the TAE disappears quickly with the frequency almost unchanged, and the EPM with lower frequency chirps down continuously. The mode frequencies and locations of the simulated EPM and TAE, as well as the chirping down feature of the EPM frequency, are consistent with the experimental measurements. The transition from EPM to TAE is found to be a self-consistent dynamic of nonlinear evolution with the expel of energetic ions due to EPM.